Aplikasi Manajemen Agenda Non-Akademik Sma Perti PPMTI Padang - syafwar, Rima; Kurniadi, Denny; Irfan, Dedy; Saputra, Hadi Kurnia (Jurnal Teknik Komputer dan Informatika, 2024)
In today's digital era, information technology has become an integral part of various aspects of life, including education. Schools, as institutions that have an important role in shaping students' character and competence, need to utilize technology to improve efficiency and effectiveness in managing various activities, including non-academic agendas. The importance of this non-academic agenda management application is based on the need to improve the quality of management of non-academic activities that can have a positive impact on student development. Through this application, SMA Perti PPMTI Padang can improve coordination between the school and students, and increase student involvement in non-academic activities. Therefore, from the description above, the author is interested in designing an application with the title "Academic and Non-Academic Agenda Management Application for SMA Perti PPMTI Padang". The author conducts research to develop academic and non-academic agenda management applications that are more effective than existing manual methods. The goal is to improve scheduling efficiency at SMA Perti PPMTI Padang, facilitate access to information for students and teachers, and reduce the administrative burden on school staff by automating administrative tasks. The method used in designing this system is the waterfall method.